La lectura comprensiva y el aprendizaje significativo. - Canchig Cajas, Angela del Pilar (2018)
The purpose of this project is to respond to one of the shortcomings in the training of students and their reading skills, reading comprehension is of utmost importance, because it allows to stimulate their cognitive - linguistic development, strengthens their personal security; an inadequate understanding of the reader affects school failure, as a consequence of anxiety, demotivation in learning and various manifestations of inappropriate behavior in the classroom, the objective of this research work was to determine the importance of reading comprehensively in the construction of meaningful learning of the students of the Eighth Year, parallel "A" of the School "Galo Vera Álvarez" of the city of Quito. For this research with a quantitative approach, numerical data was collected and analyzed on two study variables, in terms of the type of research corresponded to the field research and documentary bibliography: the methods used were of a quantitative nature such as description, analysis, induction and the deduction; The technique used was the survey, for which the questionnaire was designed and applied to the students. The contribution that is derived from this degree work constitutes a diagnosis of compliance with the fundamental skills of comprehensive reading and its various levels of depth in the students of the research institution, a study that was of great importance to diagnose curricular management.